2015
DOI: 10.1016/j.sjbs.2014.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in the body composition and bioaccumulation of heavy metals in Nile tilapia collected from drainage canals in Al-Ahsa, Saudi Arabia

Abstract: The body composition of Nile tilapia (Oreochromis niloticus) collected from drainage canals in Al-Ahsa, Saudi Arabia and the concentration of four heavy metals; zinc (Zn), cadmium (Cd), cobalt (Co) and lead (Pb) in both fish muscles and the water collected from this environment were assessed across the four seasons. The body composition was found to change with the seasons, with the best body composition being recorded in autumn and winter, where higher levels of protein (17.24, 17.65%), and fat (0.58, 0.71%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 11 publications
1
7
2
3
Order By: Relevance
“…The protein content found in this study (19.1%) was higher than the values reported in other studies on tilapia (38). However, the moisture content in this work was lower than those found by Younis et al (2015) (38) and Fonseca et al, (2013) (41), which could explain the differences found in in lipid and protein contents.…”
Section: Discussioncontrasting
confidence: 83%
See 4 more Smart Citations
“…The protein content found in this study (19.1%) was higher than the values reported in other studies on tilapia (38). However, the moisture content in this work was lower than those found by Younis et al (2015) (38) and Fonseca et al, (2013) (41), which could explain the differences found in in lipid and protein contents.…”
Section: Discussioncontrasting
confidence: 83%
“…According to these results, tilapia can be classified as a lean fish because its fat content is below 2 g fat/100 g. However, in the present study tilapia showed a lipid content of 2.8% and should, therefore, be classified as low-fat fish (total lipid content from 2% to 4%) (40). The protein content found in this study (19.1%) was higher than the values reported in other studies on tilapia (38). However, the moisture content in this work was lower than those found by Younis et al (2015) (38) and Fonseca et al, (2013) (41), which could explain the differences found in in lipid and protein contents.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations